Plant Disease Diagnosis on Vegetable Crops from Different Locations of the Country - Manandhar, Chetana; Baidya, Suraj; Manandhar, Shrinkhala; Pant, Bimala; Mahto, Baidhya N. (Journal of the Plant Protection Society, 2018)
Diseases are one of the major constraints on cultivation of crops and reduce production and productivity. Accurate disease diagnosis and proper identification is the first steps of disease management strategy. The activities of carrying out disease diagnosis help to know the distribution of the diseases in the country, explore new disease outbreak and its epidemiology, and provide information for disease management and support in research area prioritization. During fiscal year 2070/71, 252 different disease samples of different vegetable crops were received from various locations and sources for disease diagnosis. Examination of such samples identified 192 samples with fungal infection, 23 with bacterial infection, 28 with viral infection and 9 with nematode infection. In solanaceous crops, 70% disease caused by fungus and 11% by bacteria, 14% by virus and 5% by nematodes respectively. Likewise, in cucurbit crops, occurrence of pathogens is 61% fungal, 26% viral and 13% nematode respectively. The fugal pathogens were dominant in case of crucifer crops as well. The fungal pathogens were found in 79% of samples and followed by bacterial in 14% and viral in 7% respectively. Only fungal pathogen was detected in bulb and root crops. Fungal pathogens (76%) are the common problem in vegetable crops by followed by bacteria (9%) and virus pathogens (11%) and nematode (4%). The study revealed that management of fungal disease is prime concern to minimize the losses due to disease.